Pemanfaatan Aplikasi Lamikro Dalam Pengelolaan Keuangan Usaha Mikro, Kecil dan Menengah (UMKM) Kota Jayapura - Nova Herlina Bleskadit; Mariolin Anace Sanggenafa; Sara Marlyn Paru (UNIVERSITAS CENDERAWASIH, 2022)
This service activity aims to provide training on traditional (manual) accounting records by introducing large accounts in accounting books and the introduction of the Lamikro application and its use in recording daily financial transactions online to MSME actors in Jayapura City. In addition, Lamikro financial reports produced by MSME actors can be used in applying for people's business credit / KUR loans at banks. The training was held on 2 and 3 July 2021, the training was divided into 2 activities, namely on 2 July 2021 an introduction training was held on micro-applications and transaction practices encountered by business actors on a daily basis. This activity was carried out in the Accounting Department Lab and was attended by 5 people out of 10 people who registered. The activity on July 3, 2021 was carried out with assistance to every business actor in the city of Jayapura. The assistance takes place accompanied by an introduction to the recording of transactions based on the Lamikro application. In this activity, assistance was provided to 15 business actors spread across the city of Jayapura. Assistance activities are carried out by complying with applicable health procedures. Community Service Activities are also carried out pre-post tests during the implementation of the activities, with the aim of measuring the extent of understanding of the introduction material that has been given during the training process.